(untitled) (Cardiovascular Journal, 2016)
A 23 yrs old young man visited us with the complaints of a pulsatile mass in right groin and a thrill over the medial side of the right thigh which radiate to the hypogastric region for last 3 months following a stab injury on the lateral aspect of right upper thigh. He was diagnosed to have a pseudoaneurysm in common femoral artery and an arteriovenous fistula between common femoral artery and common femoral vein in same region by vascular duplex scanning and CT angiogram. We excised the aneurysm and repaired the arteriovenous fistula tract under epidural anesthesia. Finally we repaired the severed right Common femoral artery and common femoral vein. Postoperative course was uneventful. Cardiovasc. j. 2016; 8(2): 149-154